Impact analysis of cordon-based congestion pricing on mode-split for a bimodal transportation network - Meng, Qiang; Liu, Zhiyuan (Transportation research. Part C, Emerging technologies, 2012)
► Impact of a toll pattern is analyzed by a combined mode-split and traffic-assignment problem. ► Probit-based SUE and continuously distributed VOT are assumed. ► Monte Carlo simulation is used to solve the combined mode-split and traffic-assignment problem. ► A MPEC model is proposed for the optimal toll pattern with maximal total social benefit. ► The optimal toll pattern can improve the mode share of public transport to a satisfactory level. This paper investigates the impact of cordon-based congestion pricing scheme on the mode-split of a bimodal transportation network with auto and rail travel modes. For any given toll-charge pattern, its impact on the mode-split can be estimated by solving a combined mode-split and traffic-assignment problem. Using a binary logit model for the mode-split, the combined problem is converted into a traffic-assignment problem with elastic demand. Probit-based stochastic user equilibrium (SUE) principle is adopted for this traffic-assignment problem, and a continuously distributed value of time (VOT) is assumed to convert the toll charges and transit fares into time-units. This combined mode-split and traffic-assignment problem is then formulated as a fixed-point model, which can be solved by a convergent Cost Averaging method. The combined mode-split and traffic-assignment problem is then used to analyze a multimodal toll design problem for cordon-based congestion pricing scheme, with the aim of increasing the mode-share of public transport system to a targeted level. Taking the fixed-point model as a constraint, the multimodal toll design problem is thus formulated as a mathematical programming with equilibrium constraints (MPEC) model. A genetic algorithm (GA) is employed to solve this MPEC model, which is then numerical validated by a network example.